Aqueous Stable Gold Nanostar/ZIF‐8 Nanocomposites for Light‐Triggered Release of Active Cargo Inside Living Cells. (12th April 2019) - Carrillo‐Carrión, Carolina; Martínez, Raquel; Navarro Poupard, María F.; Pelaz, Beatriz; Polo, Ester; Arenas‐Vivo, Ana; Olgiati, Alessandro; Taboada, Pablo; Soliman, Mahmoud G.; Catalán, Úrsula; Fernández‐Castillejo, Sara; Solà, Rosa; et al.
Abstract: A plasmonic core–shell gold nanostar/zeolitic‐imidazolate‐framework‐8 (ZIF‐8) nanocomposite was developed for the thermoplasmonic‐driven release of encapsulated active molecules inside living cells. The nanocomposites were loaded, as a proof of concept, with bisbenzimide molecules as functional cargo and wrapped with an amphiphilic polymer that prevents ZIF‐8 degradation and bisbenzimide leaking in aqueous media or inside living cells. The demonstrated molecule‐release mechanism relies on the use of near‐IR light coupled to the plasmonic absorption of the core gold nanostars, which creates local temperature gradients and thus, bisbenzimide thermodiffusion. Confocal microscopy and surface‐enhanced Raman spectroscopy (SERS) were used to demonstrate bisbenzimide loading/leaking and near‐IR‐triggered cargo release inside cells, thereby leading to DNA staining.